(untitled) (Advances in Civil and Architectural Engineering, 2021)
The lower flow of the Neretva River (delta) covers approximately 20.000 hectares. This is a unique, humid Mediterranean area with a number of important and protected wetland habitats and is a ornithological, ichthyology, and botanical reserve. By measuring the physico-chemical parameters at 20 locations, the water quality was determined with special attention to the occurrence of salinity. Increasing salinity of the Neretva water was found, owing to inflow reduction groundwater of the river Trebišnjica and the uncontrolled deepening of the Neretva riverbed. During a one-year monitoring period, field tests were conducted of significant maritime impacts on water quality. The physical parameters were the measured temperature, conductivity, electrical resistance, salinity, chemical quantity of dissolved oxygen (expressed as a percentage, mg L-1), the oxygen pressure in water, and the pH value. The values of the above parameters were measured in the field with WTW multiparameter instruments.